Produção e caracterização de compósitos de matriz epóxi reforçada com fibra de rami para fins de reforço estrutural - Soares, Isabel Maria (2012)
The advent of modern technology has caused an increase in the use of natural resources, making it necessary the development of green technologies", which materials and technologies more environmentally frindly. Thus, various research are being conducted to ensure environmental preservation combined with the comfort and safety for the society. Among these is the use of natural fibers as reinforcement in composites, both in Brazil and in several parts of the world, because of its many social and economic advantages. This research analyze the production of epoxy matrix reinforced with ramie fibers for application as structural reinforcement material. The ramie fibers and composites with different contents (0%, 30%, 40%, 50% and 60%) and with cloth ramie (50%) was characterized for their mechanical properties, which was determined modulus of elasticity, tensile strength and maximum strain rupture. The results obtained for ramie fibers were lower than in the literature. To composites the results showed that with the increase content fibers, the mechanical properties are significant improvement, and that the composites with cloth ramie thread in the same fibers content showed improve mechanical properties. These properties were of magnitude the epoxy matrix composite with carbon fibers, with different geometric characteristics. So than, is possible to obtain a composite of epoxy matrix reinforced with ramie fibers with good performance for use as structural reinforcement.